SPEAK : a magazine for women
Poster-size reproductions of the covers of nine issues of Speak magazine: No.18, March-May 1988; No.19, April-May 1988; No.20, July-August 1988; No.21, Sept.-November 1988; No.22, Dec.1988-Jan.1989; No.23, April-May 1989; No.24, June-August 1989; No.25, October 1989; No.26, December 1989.